Enhancing Students’ Learning and Engagement through Formative Assessment using Online Learning Tools - Elbasyouny, Tariq Refaat Bahieldeen (2021)
Because of the rapid development of technology and its web- based applications and online tools, the current study sheds light on the effectiveness of online tools on both learners’ performance and their engagement. At ATA (ADNOC Technical Academy) in the United Arab Emirates, fifty students and five teachers have participated in the study by using a multiple of online tools in a six-month foundation course. Students have completed an online survey about their attitude towards the use of line tools. Structured interviews have been conducted with the teachers to answer questions about their experience of using online tools in the teaching process. A convergent parallel mixed methods approach has been followed to analyze quantitative and qualitative data. The current study has presented analytic data for students and teachers’ responses. Using descriptive analysis, the study reveals that using online tools in the learning process enhances the performance and engagement of the students in English subject.